(untitled) (The International Journal for Scientific Research, 2025)
The Kingdom of Saudi Arabia embarked on a significant legislative reform phase with the issuance of the “New Bankruptcy Law” in 2018, as part of Vision 2030, which aims to enhance business sustainability and attract investment. This research examines in-depth the extent to which the law achieves a fair balance between creditor rights and the ability to rescue distressed merchants. It also examines available legislative tools such as preventive settlement, financial restructuring, liquidation, and procedures for small bankrupts. It also analyzes implementation challenges (such as slow procedures and cross-border debt settlements), and offers practical recommendations to enhance the system’s effectiveness.